Influence of alexithymia, self-concept and health locus of control on alcohol consumption of young Portuguese - Lopes, Rosa Cristina Correia (2011)
Portugal still holds a leading place in the per capita consumption of alcohol at a world level, with high mortality rates due to hepatic cirrhosis, high indexes of road/work killings, besides a vast range of physical and mental, family and occupational health problems caused by alcohol. The narrow connection between juvenile/academic events and alcohol consumption makes youngsters vulnerable to this consumption. A descriptive-correlational and transversal study was conducted with a 552 students' sample of the Nursing degree aiming to determine some psychological characteristics that might influence/predict alcohol use/abuse in youngsters: alexithymia, self-concept and health control locus. The data collection instrument comprehended: Graffar Social Classification; Toronto Alexithymia Scale (TAS20), What Do I Think Of Health, Self-Concept Clinical Inventory (SCCI) and Alcohol Involvement Scale (AIS). Male gender is related to alcohol involvement (rho = −0.276; p = .000), revealing that 35% of the male gender and 7% of the female are normally drinkers with problems. Externally oriented thought (F3-TAS20) (rho = .084; p = .048), the impulsiveness (F4-SCCI) (rho = .119; p = .005) and the external control locus (rho = .118; p = .005) are correlated to the involvement with alcohol. Hierarchic multiple regression revealed as behaviour predictor variables of that involvement: gender (3.8%; p = .000), impulsiveness (1.4%; p = .005) and self-efficiency with inverse relation (F2-SCCI) (1.0%; p = .015). It is concluded that the choice of preventive strategies must be focused in actions that facilitate personal and social development, that promote personal and social skills, culminating in a freedom of choice by healthy behaviours and life-styles, diminishing the risk of PLA.